2014
DOI: 10.1002/pd.4342
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution chromosomal microarrays in prenatal diagnosis significantly increase diagnostic power

Abstract: High-resolution prenatal microarray testing is a reliable technique that increases diagnostic yield by at least 17.3% when compared with conventional karyotyping, without an increase in the frequency of variants of uncertain significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
3
38
3
Order By: Relevance
“…This detection rate is lower than the one reported in the literature [Callaway et al, 2013;Oneda et al, 2014;Grande et al, 2015]. The detection rate of clinically relevant CNVs is 6.5% in cases with fetal malformations detected upon ultrasound examination [Shaffer et al, 2012b].…”
Section: Discussioncontrasting
confidence: 49%
“…This detection rate is lower than the one reported in the literature [Callaway et al, 2013;Oneda et al, 2014;Grande et al, 2015]. The detection rate of clinically relevant CNVs is 6.5% in cases with fetal malformations detected upon ultrasound examination [Shaffer et al, 2012b].…”
Section: Discussioncontrasting
confidence: 49%
“…Two further cohorts, including 65 and 45 nonmalformed FGR fetuses, reported a 2-7% incremental yield [8,9]. The remaining studies had a small FGR subgroup including 3-19 cases and reported detection rates ranging from 0 to 17% in nonmalformed FGR fetuses [11,12,14,21,22] and from 0 to 21% in malformed FGR fetuses [3,11,12]. Funnel plots to assess publication bias are provided in online supplementary Figures 1S and 2S.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-two studies were excluded because they did not include an FGR group, because they included overlapping populations, or because the data required for the analysis could not be extracted. One series without an initial FGR subgroup was finally included because the authors provided us the missing data [12]. Two series from the same group were included as their most recent study included only nonmalformed FGR fetuses, while from the former only malformed FGR fetuses were included [3,9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we also observed CNV's representing known and well-documented polymorphisms or inherited benign/low risk variants for which counseling is relatively straightforward, while in our series we did not come across any (un-interpretable) variants of unknown clinical significance. This is in contrast, however, with the multitude of VOUS detected by higher resolution aCGH platforms, with figures ranging from 1-4% [48,50,51], necessitating parental follow-up studies and complicated genetic counseling and perhaps these drawbacks cannot be offset by the slightly higher detection rate.…”
Section: Resultsmentioning
confidence: 44%